RELIGION AND THE POLITICS OF NATIONALIST THOUGHT: COMPARATIVE ANALYSIS OF HINDU NATIONALISM IN INDIA AND MUSLIM NATIONALISM IN INDONESIA - Ali Munhanif; Yuli Yasin (ILMU USHULUDDIN, 2022)
The rise of religious nationalism in recent decades in developing countries has sparked attention among scholars. This article seeks to explore the political and cultural dynamics of the contemporary resurgence of religious nationalism, many of them reflected in Hindu nationalist in India and Muslim nationalist in Indonesia. We address the following question: What are the likely factors for religious-nationalist movements coming to the center stage of nation-state politics? Using the historical-institutional approach to religious politics, we argue that the forces that have driven the resurgence of religious nationalist were the interaction between the institutional design of the nation-state and the considerable opportunities for change – in a certain period of political crisis. Embedded in the issues of the institutional challenge is another series of questions that this article will address. There are variations in how and when religious-nationalist politics emerged. Why, for example, did the rise of religious politics occur in such varying ways, for instance, through a political party in India and civil society movements in Indonesia? Why did regimes or governments that promoted secular ideologies in India and Indonesia lose their hegemonic position? The answers to these questions are also largely historical-institutional. By focusing on how political institutions shape political dynamics, we suggest that institutions shape social and political outcomes, they necessarily affect people’s behavior as reflected in the politics of religious nationalism.